Associação entre o deficit estatural em crianças e caracteristicas psicossociais: rede e suporte social e saúde mental dos genitores - Cavalcante, Cristianni Gusmão (2013)
In the current context of health in developing countries, stunting in children still remains a problem of great magnitude, especially in children under five years. This nutritional problem mainly affects populations exposed to unfavorable social conditions. One factor that is negatively associated with stunting in children is impairment of mental health, as this harms the mother cares for their children. This association is seen in several studies which can not be observed when the object of investigation is the mental health of the parent. This fact is justified because of the difference in social roles that men and women engaged in traditional societies. The first function with family provider and the second function responsible for domestic and child care. As a way to improve self-confidence and life satisfaction of mothers and thus enhance the ability to tackle problems and improve the care of their children, the network and social support are possible alternatives help. This mediation is justified by the fact that the mother feel supported emotionally and / or physically. In this context, the present study investigated the association between child stunting and maternal and paternal mental health, social network, social support, and demographic and socioeconomic variables. Therefore we designed a review chapter and article results.